The effect of dope solution characteristics on the membrane morphology and gas transport properties: 2. PES/gamma-BL system - Won, J; Lee, HJ; Kang, YS (ELSEVIER SCIENCE BV, 2000)
Macrovoid-free, sponge-like membranes with improved gas permeance were obtained from a heterogeneity-developed polyethersulfone (PES)/gamma-butyrolactone (gamma-BL) dope solution. The heterogeneity of the dope solution was developed with aging time and such a heterogeneity-developed cast solution film was immersed in a nonsolvent so that it would be coagulated. In this novel procedure, the heterogeneity developed was maintained until the moment of immersion in a coagulation medium. The effect of heterogeneity in dope polymer solution on the membrane morphology as well as on gas transport properties has been studied using light scattering, atomic force microscopy (AFM) and scanning electron microscopy (SEM). Detailed roughness analysis of surface images indicates that nascent PES membranes having a finger-like structure have deep surface valleys, whereas those having a sponge-like structure have a smooth surface. Low fluidity of the dope solution due to the heterogeneity developed resulted in the membrane morphology of a sponge-like structure with a smooth surface layer. (C) 2000 Elsevier Science B.V. All rights reserved.
Keywords: ATOMIC-FORCE MICROSCOPY; LIGHT-SCATTERING; SURFACE-STRUCTURE; SPATIAL INHOMOGENEITY; CROSS-LINKING; CHARGED GELS; GELATION